Effect of premedication with intranasal dexmedetomidine or intranasal midazolam on the incidence of perioperative respiratory adverse events in children undergoing tonsillectomy and adenoidectomy: A randomized clinical trail - Sheashia, Hazem Ali Essa; Elnoury, Ahmed Said; Abdelkader, Salsabil Sayed (International journal of health sciences, 2021)
Background: Catastrophic event in paediatric anesthesia is perioperative respiratory adverse events (PRAEs), which happen twice as often in infants younger than one year old as they do in older ones. This study set out to investigate the prevalence of respiratory complications during surgery in children having tonsillectomy or adenoidectomy done. The effectiveness of midazolam and intranasal dexmedetomidine was evaluated prior to administration. Methods: This prospective randomized clinical trial was carried out on 105 children who undergoing elective tonsillectomy with or without adenoidectomy. Children were randomly assigned into three groups (35 children in each): dexmedetomidine group, midazolam group, and control group (normal saline). All PRAEs were recorded during the perioperative period till the recovery period. Results: There was a statistically significant difference in the rates of PRAEs between the dexmedetomidine group and the midazolam group, with the midazolam group exhibiting a significantly higher incidence than the control group (P value <0.05). The control and midazolam groups had a significantly higher incidence of PRAEs than the dexmedetomidine group (P value <0.05), even though there was no statistically significant difference between the two groups during the recovery phase.